The role of the Bundestag in shaping the European policy of reunited Germany - Koszel, Bogdan (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2018)
Pursuant to the German constitution, the Bundestag exercises parliamentary control over the government’s European policy. In its activities in the European Union the government must take account of the Bundestag’s proposals. The 2009 Competencies Laws strengthened the parliament’s position in European government policy, making any major decision on EU matters practically dependent on the consent of the Bundestag. According to the author, although this severely restricted Chancellor Merkel’s freedom of action, it did not paralyze the government’s European initiatives. The German Parliament behaved responsibly, especially during the financial crisis in the eurozone, allowing financial support for Greece, the establishment of the European Stability Mechanism and the establishment of the Banking Union.

Zgodnie z Ustawą zasadniczą Niemiec, to Bundestag sprawuje parlamentarną kontrolę nad europejską polityką Niemiec. Każdorazowo rząd musi informować o swoich zamierzeniach posłów. Ustawy kompetencyjne z 2009 r. wzmocniły dodatkowo parlamentarną kontrolę, uzależniając podjęcie każdej kluczowej dla losów Niemiec decyzji w Unii Europejskiej od zgody deputowanych. W opinii autora ogranicza to możliwości do działania rządu Merkel w UE, ale też nie paraliżuje jego inicjatyw. Bundestag zachowywał się odpowiedzialnie i zgodnie z wolą rządu w okresie kryzysu finansowego strefy euro, gdzie wymagana była zgoda na finansową pomoc dla Grecji, ustanowienie Europejskiego Mechanizmu Stabilności i unię bankową.
Rola Bundestagu w kształtowaniu polityki europejskiej zjednoczonych Niemiec
Keywords: united Germany; Bundestag; European politics; zjednoczone Niemcy; Bundestag; polityka europejska